Sharing Higher Education's Promise beyond the Few in Sub-Saharan Africa - Darvas, Peter; Gao, Shang; Shen, Yijun; Bawany, Bilal (Washington, DC: World Bank, 2017)
Despite a spectacular expansion of the higher education sector in Sub-Saharan Africa, the supply of tertiary education has generally failed to keep pace with demand and the region continues to lag all other regions in terms of access to tertiary education. This is in part a consequence of deeply entrenched patterns of inequitable access to higher education, and the perpetuation of what researchers refer to as “elite systems”.